Two Cases of Acute Myocardial Infarction in Patients with Severe Aortic Stenosis and Normal Coronary Arteries - Megawati Abubakar; Anggoro Budi Hartopo; M. Taufik Ismail; Real Kusumanjaya Marsam; Bambang Irawan (ACI (Acta Cardiologia Indonesiana), 2019)
In patients with aortic stenosis (AS), the development of left ventricular systolic dysfunction and heart failure predicts poor prognosis. Myocardial ischemia, particularly of the circumferential sub endocardial region, commonly occurs in patients with severe AS duringhemodynamic stress, even in the setting of angiographically documented normal coronary arteries. We report two case patients who experienced of ischemic chest pain with ST-changes and undergoing a coronary angiography but we found normo coronary arteries and echocardiography with nomokinetic. These cases highlight the importance of the correlating between history taking, physical examination and other supporting examination, especially focused on bedside investigation like echocardiography in the management of patients presenting with chest pain.